Effect of introducing plyometric training for track-and-field athletes in season - Kobayashi, Y.; Terada, K.; Yamamoto, D. (Japan Journal of Physical Education, Health and Sport Sciences, 2018)
We conduct a randomized controlled trial to clarify the effect of introducing plyometric training (PLY) to track-and-field athletes in season for conditioning and various performances such as jumping and sprinting ability. The study subjects were 14 male athletes from the T University track and field team specialized in sprinting, jumping, and combined events. Among these athletes, seven underwent ordinary training plus 8 weeks of PLY (group T), while seven underwent ordinary training only (group C). After taking into consideration their physique, competitive event specialization, and competition record, the athletes were randomly assigned to the two groups. Measurements were performed on the athletes in both groups before the intervention, in the fourth week, and upon completion of the intervention. We found that, in the intervention group, the rebound drop jump index value, and the right and left lateral vastus muscle thickness exhibited interaction with the length of the intervention period. In other words, these values showed a tendency to increase in group T relative to group C as the intervention period proceeded. However, no significant differences in the values for various conditioning indicators were observed between the two groups during the intervention period. Our study results indicate that this PLY intervention is able to enhance muscle volume and certain aspects of jumping ability, such as those using the stretch shortening cycle movement. Moreover, within the range of the load intensity used in this study, the intervention was implemented safely without causing any decrease in conditioning, indicating that it could be useful as a training method for track-and-field athletes in season.